Catalytic Activity of Microbially‐formed Palladium Nanoparticles. Issue 2 (12th December 2017) - Yang, Sarah A.; Nordmeier, Akira; Chidambaram, Dev
Abstract: The catalytic behavior of microbially‐formed palladium nanoparticles using Clostridium pasteurianum BC1 is reported. To our knowledge, this is the first study that evaluates the electrochemical catalytic activity of microbially‐formed palladium nanoparticles. Pd nanoparticles formed using immobilized microbes were found to exhibit an average mass activity of 177 mA mg −1 which was almost twice the activity of the abiotically formed controls (94 mA mg −1 ). The results of this study aim to support the use of nanoparticles formed using facile and environmentally‐friendly microbial synthesis methods as a suitable alternative as opposed to standard physical and chemical synthesis methods. Abstract :